VD_FINDINFO HC / 2020 / 363 vom 2. Juni 2020 - VD Tribunal cantonal (2020)
EXPULSION DE LOCATAIRE, DÉCISION D'IRRECEVABILITÉ, OBSERVATION DU DÉLAI | 138 CPC (CH), 248 let. b CPC (CH), 314 al. 1 CPC (CH)